Accountability practices in microfinance: cultural translation and the role of intermediaries. Issue 7 (17th September 2018) - Marini, Lisa; Andrew, Jane; van der Laan, Sandra
Abstract : Purpose: The purpose of this paper is to explore how accountability practices are affected and potentially transformed when mediated by translation. Adopting a postcolonial lens, the authors consider the ways in which translation functions and how intermediaries act as cultural translators in the context of microfinance. Design/methodology/approach: The authors take a qualitative approach to a case study of a microfinance organization based in South Africa. Fieldwork allowed for the collection of data by means of direct observations, interviews, documents and a fieldwork diary. Findings: The study demonstrates the presence of spaces of hybridity that co-exist within the same organizational context (Bhabha, 1994 ). Two spaces of hybridity are highlighted, in which translation processes were possible because of the proximity between borrowers and fieldworkers. The first space of hybridity was found locally and here translation shaped an accountability that aimed at leveraging local cultures and favoring cultural framing. The second space of hybridity was characterized by the interaction between oral and written cultures and the translation of responsibilities and expectations was predominantly unidirectional, prioritizing accountability practices consistent with organizational requirements. Originality/value: This research offers in-depth insights into the links between intermediation, translation and accountability practices. It differs from prior research in considering intermediaries as active translators of accountability practices who act in-between cultures. The authors contend that the translation process reinscribes culture allowing dominant accountability practices to prevail and local cultural traditions to merely contextualize accountability practices.